Predicting Energy Savings Associated with Falling-Film Drain Water Heat Recovery Systems in Residential Buildings - Manouchehri, Ramin (University of Waterloo, 2024)
Falling-film drain water heat recovery (DWHR) systems are heat exchangers utilized for recovering thermal energy from water travelling down shower drains in residential buildings. There are many commercially available DWHR heat exchangers on the market, and there exist a large variety of shower conditions that change from one house to another. For instance, the showerhead fixture and its associated flowrate, shower temperature and the plumbing system in a house are variables that directly impact energy savings, which can vary significantly between different houses and occupants. Clearly, reliable modeling procedures must be created to account for the large variety of operating conditions for DWHR heat exchangers. The main goals for this project were to create and validate robust models to predict energy savings during steady-state and transient conditions, and to use these models in a building simulation software to identify the significance of plumbing configuration on energy savings. To this end, a thorough review of the literature concerning heat exchangers was done to identify the best procedure for modelling DWHR systems. For the steady-state analysis, a novel procedure was devised to derive correlations for the heat transfer coefficients in terms of heat transfer fundamentals. A semi-empirical correlation was also devised to allow faster calculations in cases where correlations for heat transfer coefficients are not readily available. Both methods were validated and were shown to have a mean absolute error smaller than 4%. Additionally, expressions for the transient behaviour of DWHR systems were derived based on heat exchanger theory and it was shown that these heat exchangers can be represented as first-order systems. Experimental data showed that the time constants associated with the typical operation of DWHR systems were generally on the order of a few seconds. Next, the steady-state and transient models were programmed into TRNSYS (Transient System Simulation Tool) to perform monthly simulations to predict energy savings. For simulation purposes, five distinct plumbing configurations were considered, which covered all possible methods a DWHR heat exchanger can be incorporated into the plumbing system for a house. Identical draw schedules were devised and applied to all simulations, and the overall energy consumptions for all simulations were estimated and compared with a base case (i.e. a plumbing system without a heat exchanger). The results showed that small changes in plumbing configuration can have significant impact on the energy savings that can be achieved using DWHR heat exchangers. For instance, the results for one of the simulated heat exchangers showed that the energy savings can range from 25% to 35% depending on the plumbing configuration. These findings were then used as a basis to formulate how DWHR heat exchangers should be modeled, and perhaps more importantly, to highlight the urgent need to update the current building codes and standards to better reflect the actual performance for this particular heat exchanger technology.
Keywords: heat exchanger; drain water heat recovery